Trans joy: a space for self-realisation, resistance and intersectional community building - Lehvä, Mari (My University, 2023)
This thesis is a qualitative study that explores the topic of trans joy and its presence in the everyday lives of trans and non-binary people. It contributes to efforts of addressing the severe gap in research literature that currently exists on the topic of trans joy. The data for the thesis consists of 6 semi-structured, in-depth interviews and 5 written reflections. Voluntary sampling was used to recruit participants via two trans and queer focused online community platforms. Thematic content analysis was applied to the data in a recursive, ongoing manner to account for divergent viewpoints, paying particular attention to the exploratory nature of the thesis and the fact that trans joy is an emergent topic in research. The research questions were: 1) what is trans joy, and more specifically: what brings people trans joy, what does it mean for people and what are its impacts?, and 2) can trans joy act as a form of resistance against systems of oppression and if so, how? This thesis found that trans joy allows people to grow more connected and visible to themselves, that it centres the variety and creativity involved in people’s gender journeys and that its impacts included newfound confidence and self-understanding, increased quality of life, an ability to envision a more fulfilling future, a firm sense of agency and a greater ability to support others. It also found that trans joy can contribute to new conceptualisations of dysphoria and euphoria: where previously dysphoria has been understood as a primary catalyst or prerequisite for transition, trans joy highlights that a vision for joy and contentment can be an equally significant motivation. To answer the question on resistance, this thesis brings together a body of literature on transnormativity, interrogating its oppressive functions for the ways in which they impact trans people’s community building practices and disrupt social connections. The key findings in relation to this question were the importance of being in community, the potential of trans joy to comment on, question and re-frame existing transnormative understandings, its ability to highlight social conditions which expect trans people to be visible only strategically and its ability to facilitate spaces where trans people’s personhoods can exist with a wholeness. This research shows that trans joy has a multifaceted significance both in trans people’s personal lives and in the cultural contributions it can make for understanding gender transitions and the value of gender diversity more broadly. Its findings call for further research on trans joy across different settings, and for practical applications of trans joy where the provision of transition-related health care is protected and gender-affirming spaces for trans people are created across society.
Keywords: trans joy, trans studies, gender euphoria, transnormativity, intersectionality, personhood, desire, resistance, visibility, community